2017 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2017
DOI: 10.1109/bibm.2017.8217820
|View full text |Cite
|
Sign up to set email alerts
|

Deep gramulator: Improving precision in the classification of personal health-experience tweets with deep learning

Abstract: Health surveillance is an important task to track the happenings related to human health, and one of its areas is pharmacovigilance. Pharmacovigilance tracks and monitors safe use of pharmaceutical products. Pharmacovigilance involves tracking side effects that may be caused by medicines and other health related drugs. Medical professionals have a difficult time collecting this information. It is anticipated that social media could help to collect this data and track side effects. Twitter data can be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…A set of 22 engineered features based upon both textual content and metadata of tweets was proposed in constructing a corpus of personal experience tweets (Jiang et al, 2016). Subsequently, Calix and colleagues introduced the concept of deep gramulator to include a textual feature that contains expressions in one class but not in the opposite class, to improve the discriminatory ability of the classification (Calix et al, 2017). Advancement in neural embedding, which demonstrated state-of-art results in many classification tasks on textual data, motivated the development of a new approach of combining word embedding (word2vec) and a recurrent neural network which demonstrated a significant improvement of classification performance (p < 0.05) (Jiang et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…A set of 22 engineered features based upon both textual content and metadata of tweets was proposed in constructing a corpus of personal experience tweets (Jiang et al, 2016). Subsequently, Calix and colleagues introduced the concept of deep gramulator to include a textual feature that contains expressions in one class but not in the opposite class, to improve the discriminatory ability of the classification (Calix et al, 2017). Advancement in neural embedding, which demonstrated state-of-art results in many classification tasks on textual data, motivated the development of a new approach of combining word embedding (word2vec) and a recurrent neural network which demonstrated a significant improvement of classification performance (p < 0.05) (Jiang et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Calix et al [18] proposed a deep-learning-based medication-use safety scheme called the Deep Gramulator, which tracks and monitors the use of medication by medical personnel to facilitate medication-use safety. The Deep Gramulator can automatically extract tweets to obtain relevant personal health experiences from social media.…”
Section: Related Workmentioning
confidence: 99%
“…Text classification with deep learning is considered better than machine learning [12] on the same object. A previous study [13] showed that the results of deep learning accuracy were better than machine learning in the classification of health tweets. The superior performance of deep learning than machine learning underlies this research using deep learning as a classification method.…”
Section: Introductionmentioning
confidence: 97%